The History Narration of Peer Faiz-ul-Amin Farooqi Sialvi - Naureen, Afshan; Ghumman, Muhammad Naeem; Ullah, Hafiz Utban (sourcecoder, 2023)
Pir Faizul Amin Farooqi Sialvi's Tarikh Gui Khanqah Munian is a Chishti Sialvi Khanqah in Chakuri Sharif, Gujarat. The distinguishing feature of this monastery is that the tradition of historiography which was our classical tradition has been refreshed and innovated. Pir Faizul Amin, the Sajjada Nashin of Khanqah Munian Sharif, had a perfect skill in history. He used to say history in Arabic, Persian and Urdu. In the current era, he has given a new dimension to history. In the circles of Urdu literature, the practice of history telling is non-existent. In such an environment, Chishti Darvish, sitting in a remote monastery, was not only keeping this genre alive, but he was very knowledgeable in this art. History is a difficult art. He had perfect access to the fields of history. His book "Infs al-Turikh" is important in this context, in which he has mentioned the birth or death history of the famous elders and Mashaikhs from the birth of the Holy Prophet to the present era. His main art is history, he has expertise in history. He has written sections of history on the death of many scholars. You have recited parts of history in Persian, Urdu and Arabic. In the past, poets started telling history even on small events.